Effects of thermal processing on E. coli K12 in black tea leaves - Mills, McKenna; Savage, Sierra; Sevart, Alexander; Rettig, S.; Samskey, S.; Ochs, J.; Perla, R.; Reeder, C.; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: Escherichia coli bacteria is usually found in the digestive tract of living things. Most E. coli strains do not cause harm. However, there are pathogenic strains, they can lead to illness and start to cause damaging symptoms such as diarrhea and inflammation of the intestinal tract. Pathogenic E.coli continues to consistently effect a wide range of products from meat to fruit & vegetables. Many producers are finding that low risk products are becoming contaminated. Little is known about the presence of E. coli in dried products, such as tea leaves Purpose: The objective of this study was to test two different thermal processing times to determine how long the product must be under extended heat to bring the E.coli levels down to acceptable standards. Methods: The tea leaves were inoculated with E.coli and put into a commercial oven. Temperature probes were inside the bags of ground black tea and were watched carefully to see when they reached 70℃. Once the samples reached 70℃, the samples were timed. Sample A was taken out at 1 minute, Sample B was taken out at 5 minutes. 270 samples were plated using aseptic lab techniques, this included the positive control, negative control, method 1, and method 2. Results: Both heat treatments methods proved to be effective in eradicating the inoculated E. coli. Out of the 36 E. Coli plates plated for Treatment 1 and 2, only 2 had countable growth (5.5%). The treatment’s p values were ≤ 0.05 indicating strong evidence against the null hypothesis. Significance: The results show that either method would be successful for the producer.
Keywords: Fall 2017